What is a Family? : answers from early modern Japan - Schaeffer, Edith; Berry, Mary Elizabeth, 1947-; Yonemoto, Marcia, 1964- (2019)
"What Is a Family? explores stories of the Japanese family under the political and social order established by the Tokugawa shogunate (1603-1868). This period showed variation in the ways that families navigated constraints and opportunities. But the circumstances and choices that made one family unlike another were framed, then as now, by the prevailing laws, norms, and controls on resources that shaped all lives. The selected family accounts in this collection of essays focus on a wide variety of individuals ranging from military elite to agrarian villagers and communities of outcastes. Each chapter incorporates diverse sources--from population registers and legal documents to personal letters and diaries--while combining wide accounts of collective practices with intimate portraits of individual actors"--Provided by publisher.
Introduction / Mary Elizabeth Berry and Marcia Yonemoto -- The language and contours of familial obligation in fifteenth- and sixteenth-century Japan / David Spafford -- Adoption and the maintenance of the early modern elite : Japan in the East Asian context / Marcia Yonemoto -- Imagined communities of the living and the dead : the spread of the ancestor-venerating stem family in Tokugawa Japan / Fabian Drixler -- Name and fame : material objects as authority, security and legacy / Morgan Pitelka -- Outcastes and Ie? : the case of two beggar guilds / Maren Ehlers -- Governing the samurai family in the late Edo period / Luke Roberts -- Fashioning the family : a temple, a daughter, and a wardrobe / Amy Stanley -- Social norms versus individual desire : conventions an unconventionality in the history of Hirata Atsutane's family / Anne Walthall -- Family trouble : views from the stage and a merchant archive / Mary Elizabeth Berry -- Are all happy families alike? : reading the idealized family in print at the turn of the nineteenth century / David Atherton.
Includes bibliographical references and index.
Keywords: Families -- Japan -- History -- Edo period, 1600-1868.; Japan -- Social life and customs -- 1600-1868.; Japan -- History -- Tokugawa period, 1600-1868.